Long-Term Outcomes of Nonadherence to Anti-VEGF Therapy in Advanced Neovascular Age-Related Macular Degeneration - A. N. Kulikov; V. R. Zhalimova; D. S. Maltsev (Oftalʹmologiâ, 2022)
Purpose: To study long-term outcomes in neovascular age-related macular degeneration (nAMD) patients with low visual acuity and nonadherence to a treatment regimen of anti-vascular endothelial growth factor (VEGF) therapy.Patients and methods. In this study we included nAMD patients with best corrected visual acuity lower than 0.1 decimal equivalent, nonadherent to anti-VEGF therapy (13 eyes, group I), treatment-naïve (15 eyes, group II) or nonadherence to anti-VEGF therapy followed by termination of anti-VEGF treatment (18 eyes, group III). All participants received comprehensive ophthalmic examination and optical coherence tomography baseline and at the end of the follow-up period.Results: In group I, 7.6 ± 4.3 intravitreal anti-VEGF injections were performed over a mean period of 38.9 ± 27.5 months. In group II, a mean follow-up was 31.7 ± 28.6 months. In group III 4.8 ± 2.2 intravitreal anti-VEGF injections were performed over a mean period of 26.9 ± 26.4 months followed by treatment discontinuation for a mean period of 24.6 ± 18.6 months. None of study groups showed statistically significant changes in BCVA or an increase of central retinal thickness (p > 0.05). At baseline all study eyes frequently demonstrated severe morphological changes in the macula including atrophy of retinal pigment epithelium (RPE), subretinal fibrosis, RPE tear, or giant intraretinal cysts.Conclusion: In nAMD patients with low BCVA and severe anatomical changes in the macula nonadherence to a treatment regimen of anti-VEGF therapy results in non-superior long-term outcomes compared to natural course of the disease.